Electrocardiographic and Echocardiographic Predictors of Atrial Fibrillation in Patients With Hypertrophic Cardiomyopathy - Mandeş, Leonard; Roşca, Monica; Ciupercă, Daniela; Călin, Andreea; Beladan, Carmen C.; Enache, Roxana; Cuculici, Andreea; Băicuş, Cristian; Jurcuţ, Ruxandra; Ginghină, Carmen; Popescu, Bogdan A. (Frontiers in Cardiovascular Medicine, 2022)
Background Patients with hypertrophic cardiomyopathy (HCM) have an increased prevalence of atrial fibrillation (AF) compared to the general population, and left atrium (LA) remodeling is strongly correlated with the risk of AF. This prospective, monocentric study aimed to assess the role of LA electrocardiographic and echocardiographic (structural and functional) parameters in predicting the risk for incident AF in patients with HCM. Methods and Results The study population consisted of 126 HCM patients in sinus rhythm (52.6 ± 16.2 years, 54 men), 118 of them without documented AF. During a median follow-up of 56 (7–124) months, 39 (30.9%) developed a new episode of AF. Multivariable analysis showed that LA booster pump function (assessed by ASr, HR = 4.24, CI = 1.84–9.75, and p = 0.038) and electrical dispersion (assessed by P wave dispersion – Pd, HR = 1.044, CI = 1.029–1.058, and p = 0.001), and not structural parameters (LA diameter, LA volume) were independent predictors of incident AF. Seventy-two patients had a LA diameter < 45 mm, and 16 of them (22.2%) had an AF episode during follow-up. In this subgroup, only Pd emerged as an independent predictor for incident AF (HR = 1.105, CI = 1.059–1.154, and p = 0.002), with good accuracy (AUC = 0.89). Conclusion Left atrium booster pump function (ASr) and electrical dispersion (Pd) are related to the risk of incident AF in HCM patients. These parameters can provide further stratification of the risk for AF in this setting, including in patients considered at lower risk for AF based on the conventional assessment of LA size.